Comparison of Wet Destruction, Dry Ashing, and Acid Homogenic Methods In Determining Na And K in Beef and Chicken Using Flame Photometer - Herlinawati Herlinawati; Normalina Arpi; Nurul Azmi (Universitas Negeri Medan, 2020)
This research was purposed to compare the yield of destruction method in determining sodium (Na) and potassium (K) content in beef and chicken by using flame photometer. The destruction methods used they are wet destruction, dry ashing, and acid homogenic method. In acid homogenic method two types of acid are used as solvents are HCl and HNO3 with concentration variation of 0.5 M; 1 M; and 1.5 M. While the wet destruction method uses a mixture of concentrated HNO3 and HClO4 (1: 2) and the dry ashing method uses only HNO3. The highest Na content obtained from the three methods after being analyzed by Analysis of Variance (ANOVA) and the Smallest Significant Difference (SSD) test was found in the dry ashing method that is 86.33 mg Na in beef, when compare with the literature is around 64 – 69 mg. While the highest K content was found in acid homogenic method using HCl solvent is 618.77 mg K in beef, when compare with the literature is around 334 – 355 mg.